1989
DOI: 10.2503/jjshs.58.327
|View full text |Cite
|
Sign up to set email alerts
|

Promotive Effects of Exogenous and Endogenous Gibberellins on the Fruit Development in Cucumis sativus L.

Abstract: SummaryPromotion of development of cucumber fruit (Cucumis sativus L. cv. Chojitsuochiai No. 2) was achieved by the application of gibberellin A3 (GA3) and gibberellin A4+7 (GA4+7) to its flower. The promotive activity of GA4+7 was much greater than that of GA3. Their activities increased in parallel with higher concentrations.The promotive activities of gibberellin A4 (GA4) and gibberellin A7 (GA7) were also higher than GA3.The level of endogenous gibberellins in the placental tissue and the sarcocarp of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However, the application of IAA and GA 3 to a parthenocarpic cultivar led to the inhibition of fruit growth at the middle and upper nodes in our study. Conversely, Shimizu (1967), Ogawa et al (1989), and Hayashi et al (1970) found that the IAA and GA 3 treatments of a single fruit per plant induced parthenocarpic fruit growth in non-parthenocarpic cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the application of IAA and GA 3 to a parthenocarpic cultivar led to the inhibition of fruit growth at the middle and upper nodes in our study. Conversely, Shimizu (1967), Ogawa et al (1989), and Hayashi et al (1970) found that the IAA and GA 3 treatments of a single fruit per plant induced parthenocarpic fruit growth in non-parthenocarpic cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit were weighed, frozen in liquid nitrogen, and then the concentrations of trans-zeatin (Z), trans-zeatin riboside (ZR), isopentenyladenine (iP), isopentenyladenosine (iPR), and IAA were determined. These hormones are active forms of auxin and cytokinin that function as primary inducers of fruit growth in cucumber plants (Kim et al, 1992;Ogawa et al, 1989Ogawa et al, , 1990. The extraction and purification of hormones were performed as described by Yu et al (2001) and Ito et al (1999), with some modifications (Boonkorkaew et al, 2008).…”
Section: Endogenous Hormone Analysismentioning
confidence: 99%
See 3 more Smart Citations